DNA barcoding using ITS2 for identification of Labisia pumila in selected Malaysia herbal medicinal product - Fatin Liyana Yusli, 1995-, author 614759 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Sains (Biologi)) - Universiti Teknologi Malaysia, 2018